If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-3x + -6)(x + -1) = 0 Reorder the terms: (-6 + -3x)(x + -1) = 0 Reorder the terms: (-6 + -3x)(-1 + x) = 0 Multiply (-6 + -3x) * (-1 + x) (-6(-1 + x) + -3x * (-1 + x)) = 0 ((-1 * -6 + x * -6) + -3x * (-1 + x)) = 0 ((6 + -6x) + -3x * (-1 + x)) = 0 (6 + -6x + (-1 * -3x + x * -3x)) = 0 (6 + -6x + (3x + -3x2)) = 0 Combine like terms: -6x + 3x = -3x (6 + -3x + -3x2) = 0 Solving 6 + -3x + -3x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(2 + -1x + -1x2) = 0 Factor a trinomial. 3((1 + -1x)(2 + x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Subproblem 2
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Solution
x = {1, -2}
| a+0+y+d+e=d(0) | | -5x(5x-5)= | | x+(-7)=-15 | | 5(x-3)-2(x+4)=(x-3)+4(x-1) | | a^4-a^2+5=0 | | 3(x+8)=38-4x | | cos3y=1/2 | | 3x^2+41x-170=0 | | X-(2x+5)=-2(x+4)+19 | | -(2x+5)=2(x+4)+19 | | 60x/120x | | 4(x+4)=2(x+20) | | -8(3y+5)+y=-1 | | 25x+20=5x+40 | | 6x+18=-10 | | 2(-2y+5)-y=-5 | | 3(1.8+-0.4y)-y=8 | | 3y+25=2y+50 | | logy=alogx+b | | 9+-4y=9-4y | | -6x-5y=1 | | 4+3y-3y=4 | | 9n+68=7n+2n-2 | | 0=-4-4x-3x^2 | | 19+(-4y)+4y=19 | | 9x+1=3x-7 | | 9x+1=3x-1 | | 3(4+-2y)+4y=10 | | Y=-4/7x-1/7 | | 15x^2+40x-5=0 | | log(x)=0.40338 | | n^2-12n+21=0 |